FRAMING PENGUNGKAPAN RISIKO SIBER: ANALISIS KONTEN LAPORAN TAHUNAN TELKOM INDONESIA (Az-Zaida: Jurnal Ilmu Multidisiplin, 2025)
Cyber risks have become a material issue in the governance of digital-based corporations, particularly within the telecommunications sector that manages nationally critical infrastructure. However, the maturity of cyber risk disclosure in Indonesian annual reports remains inconsistent, raising questions about how cyber risks are identified, mitigated, and framed within corporate reporting practices. This study focuses on Telkom Indonesia to examine how cyber risks are articulated in annual reports, how governance structures and mitigation mechanisms are presented, and how risk narratives are linked to regulatory compliance and business strategy. Using a case study design and qualitative content analysis, the study analyzes Telkom’s 2020–2024 annual reports at the paragraph level through a deductive–inductive category framework encompassing risk identification, mitigation, governance, impacts, and strategic responses. The findings reveal a shift in disclosure from compliance-oriented narratives toward strategic framing aligned with strengthened governance and digital transformation. Network infrastructure and operational risks emerge as stable core risks, whereas privacy and data breach risks evolve from regulatory obligations into strategic risks with reputational implications. Recurring cyberattacks since 2022 indicate increasing maturity in risk identification. Mitigation is carried out through technical, operational, and organizational controls integrated with internal control systems. Telkom’s cyber risk disclosure is governance-driven and framed as part of the company’s digital strategy as well as a mechanism for legitimizing corporate accounting disclosures. These findings contribute to the accounting and risk disclosure literature by demonstrating how a national digital corporation constructs cyber risk as an integral component of governance and corporate strategy.